2019
DOI: 10.1002/dev.21938
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal depression and mother and infant oxytocin receptor gene (OXTR_rs53576) polymorphisms

Abstract: Polymorphisms in the oxytocin receptor gene, OXTR_rs53576, have been linked to differences in maternal sensitivity and depressive symptoms. Although some studies suggest the A allele confers risk for mood disorders, individuals homozygous for the G allele may exhibit greater sensitivity to both positive and negative social experiences, including in the mother-infant dyad. Given the bi-directional nature of mother-infant influences on maternal mood, we tested the association between both mothers' and infants' O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…According to previous research consistent with a diathesis-stress model ( Augustine et al., 2018 ), rs53576 A-allele was frequently associated with psychopathologies correlated with an increased sensitivity to stress ( Saphire-Bernstein et al., 2011 ; Choi et al., 2019 ). Despite the suggestion that individuals homozygous for the G-allele may exhibit greater sensitivity to social experiences ( Asherin et al., 2019 ), the present findings oppositely demonstrated that A-allele carriers appeared to be more sensitive to parenting style (presumably, to the level of paternal interest in their lives) compared to those with GG genotypes. Therefore, together with the “plasticity genes model” the data obtained allow to hypothesize that A-allele is a plasticity marker, contributing to a greater sensitivity to both positive and negative environmental influences.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…According to previous research consistent with a diathesis-stress model ( Augustine et al., 2018 ), rs53576 A-allele was frequently associated with psychopathologies correlated with an increased sensitivity to stress ( Saphire-Bernstein et al., 2011 ; Choi et al., 2019 ). Despite the suggestion that individuals homozygous for the G-allele may exhibit greater sensitivity to social experiences ( Asherin et al., 2019 ), the present findings oppositely demonstrated that A-allele carriers appeared to be more sensitive to parenting style (presumably, to the level of paternal interest in their lives) compared to those with GG genotypes. Therefore, together with the “plasticity genes model” the data obtained allow to hypothesize that A-allele is a plasticity marker, contributing to a greater sensitivity to both positive and negative environmental influences.…”
Section: Discussioncontrasting
confidence: 99%
“…To date multiple efforts to unravel GxE interactions affecting depression-like behavior have been conducted, which demonstrated the interrelation of stress-related factors occurred at pre- and postnatal levels of development and OXTR gene polymorphisms. These studies reported a modulating effect of childhood adversity experienced by responders ( Park et al., 2019 ) or by their mother in childhood ( Elwood et al., 2019 ; Mileva-Seitz et al., 2013 ), maternal postnatal depression ( Choi et al., 2019 ), and even their child's OXTR genotype ( Asherin et al., 2019 ). Previously, an interaction between OXTR rs2254298 and the quality of the parental environment was reported to affect symptoms of depression and anxiety in female adolescents ( Thompson et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar patterns of methylation density in oxytocin receptor gene were observed in women with perinatal depression and with insecure attachment style, which indicates association between those two characteristics [43]. Moreover, it was proposed that infants' oxytocin receptor genotype might also alter the behaviour of mothers who exhibit depressive characteristics [44]. Oxytocin seems to interact also with serotonergic system.…”
Section: Exogenous Oxytocinementioning
confidence: 68%
“…As evidenced above, the published conclusions on the role of OXTR polymorphism and methylation in depression are contradictory, making the question unanswered. There were further studies showing the influence of the rs53576 polymorphism on different aspects of depression, such as negative social interactions [ 74 ], prepulse inhibition of the startle reflex and startle reactivity [ 75 ], interpersonal risk factors [ 76 ], suicide attempts [ 77 ], hippocampal volume [ 78 ], effects of social environment on postpartum depression [ 79 , 80 ], negative affectivity [ 81 ], trauma-related psychopathology [ 82 ], and work stress [ 83 ]. However, other reports presented results showing no correlations between depression and the rs53576 polymorphism in the OXTR gene [ 84 , 85 , 86 , 87 , 88 ].…”
Section: Oxtr In Mental Disordersmentioning
confidence: 99%